2019
DOI: 10.21018/rjcpr.2019.1.269
|View full text |Cite
|
Sign up to set email alerts
|

Users’ Perspective on the Credibility of Social Media Influencers in Romania and Germany

Abstract: The present research addresses the issue of source credibility of social media influencers from the perspective of users. Social media influencers are defined as online personalities with a large number of followers, across one or several social media platforms. They have a complex role, being content creators, online opinion leaders, and even entrepreneurs. Influencer marketing is becoming a more and more relevant component of current advertising campaigns worldwide. A consistent body of literature has underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 46 publications
3
53
0
Order By: Relevance
“…Xiao et al (2018) found that the trustworthiness and the social influence of YouTubers affect the perceived information credibility on YouTube. Furthermore, Balaban and Mustățea (2019) showed that attractiveness, trustworthiness, expertise, and similarity are essential factors affecting the perceived information credibility, at least in Romania and Germany. The evaluation of these factors may be additionally moderated by the gender of both the media user and the influencer (Todd & Melancon, 2018).…”
Section: Evaluation Of Youtubers and Ytps-videosmentioning
confidence: 99%
“…Xiao et al (2018) found that the trustworthiness and the social influence of YouTubers affect the perceived information credibility on YouTube. Furthermore, Balaban and Mustățea (2019) showed that attractiveness, trustworthiness, expertise, and similarity are essential factors affecting the perceived information credibility, at least in Romania and Germany. The evaluation of these factors may be additionally moderated by the gender of both the media user and the influencer (Todd & Melancon, 2018).…”
Section: Evaluation Of Youtubers and Ytps-videosmentioning
confidence: 99%
“…Followers believe influencer endorsements represent a public display of the influencer’s intrinsic taste, rather than a violation of their followers’ trust (McQuarrie et al, 2013). Furthermore, viewers and followers identify with influencers as the relatable girls or guys next door, and as such perceive influencers as a credible source of information (Balaban and Mustatea, 2019). For example, in contrast to inaccessible traditional celebrities, influencers engage in direct conversations with and connect with their followers through their social media (Balaban and Mustatea, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, viewers and followers identify with influencers as the relatable girls or guys next door, and as such perceive influencers as a credible source of information (Balaban and Mustatea, 2019). For example, in contrast to inaccessible traditional celebrities, influencers engage in direct conversations with and connect with their followers through their social media (Balaban and Mustatea, 2019). Moreover, influencers often establish themselves as experts in specific domains, adding to their credibility as sources for product promotion in the eyes of their followers (Balaban and Mustatea, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The popularity enjoyed by influencers shows the potential that may be valorised by those who use virtual space and digital communication, be it individuals or organisations. 31 Until recently, we would invest in opinion leaders capable of shaping communication in the public sphere. Today, things seem to change in favour of social networks and of those that can influence the personal decisions of those connected to the new technologies in the virtual space.…”
Section: Philosophical Counselling and The Challenges At Personal Level Brought By Personal Brand Development In Virtual Spacementioning
confidence: 99%